Tardigrada of Grand Cayman, West Indies, with descriptions of two new species of eutardigrade, Doryphoribius tessellatus (Hypsibiidae) and Macrobiotus caymanensis (Macrobiotidae) - Meyer, Harry A. (Zootaxa, 2011)
Terrestrial tardigrades were collected from moss, lichen and leaf litter from Grand Cayman in the Cayman Islands, West Indies. Six species were found. Milnesium tardigradum Doyère, 1840, Minibiotus intermedius (Plate, 1889), Paramacrobiotus areolatus (Murray, 1907) and P. richtersi (Murray, 1911) have been reported previously from other islands in the Caribbean Sea. Two species on Grand Cayman were new to science. Doryphoribius tessellatus sp. n. belongs to the ‘eveli- nae-group’, with two macroplacoids and cuticular gibbosities. In having two pairs of posterior gibbosities and cuticular depressions forming a reticular design, it is most similar to Doryphoribius quadrituberculatus Kaczmarek & Michalczyk, 2004 from Costa Rica. It differs from D. quadrituberculatus in its gibbosity sequence (III:4:2:2), the number of teeth, size of macroplacoids and details of the reticular design on the dorsal cuticle. Macrobiotus caymanensis sp. n. belongs to the ‘polyopus-group’ of species. It differs from other species of the group in having a shorter buccal tube, a more posterior stylet support insertion point and fewer, larger egg processes.